Implementasi Kurikulum Tersembunyi dalam Pembangunan Karakter Siswa (Studi Kasus di SMA Negeri 3 Palu) - Elya, Elya (Hunafa: Jurnal Studia Islamika, 2021)
The purpose of this study was to find out about the implementation of the hidden curriculum in the character development of students at SMA Negeri 3 Palu, the focus of which is: (1) How is the implementation of the hidden curriculum in SMA Negeri 3 Palu; (2) How to design the hidden curriculum in developing the character of students; (3) the impact of implementing the hidden curriculum. This research uses qualitative methods with an in-depth case study approach. Data collection techniques through observation, in-depth interviews, and documentation. Meanwhile, data analysis through descriptive, data reduction, verification, and data presentation. The results showed that the implementation of hidden curriculum in the school learning program and became strengthening, both in the academic and non-academic fields of students. As a result, the level of compliance and discipline of students has increased, such as discipline in the implementation of congregational prayers (dhuha and dzuhur prayers), activeness in religious studies, social care, empathy, tolerance, and a caring attitude towards the environment. The hidden curriculum design is formed from the existence of the school's vision and mission, rules, policies, and school discipline continuously, and through the exemplary and habituation of parents, school principals, educators, and other school members. The impact of the hidden curriculum in the character development of students at SMA Negeri 3 Palu on the moral and spiritual attitudes of students is quite positive. The final examination scores increased and the achievements in participating in various competitions were quite significant at the local, national and international levels. Significant impact on the quality of the school which has now been declared as a tourist destination school and towards the ASEAN Eco-School Award. The implications of this research are expected for curriculum experts, education practitioners, school principals, academic educators to study, giving more and more flexible portions of time to non-academic programs and activities, enrichment based on morals and spirituality. To explore the factors that affect the hidden curriculum, it is necessary to carry out further research using a quantitative approach.